MATHEMATICAL CONNECTION ABILITY INSTRUMENT FOR PRIMARY SCHOOL STUDENTS - Hafiziani Eka Putri; Cahya Karisma Pertiwi; Aisyah Herlina Arrum; Rifa Nurhanifa; Aan Yuliyanto (Auladuna: Jurnal Pendidikan Dasar Islam, 2021)
AbstractThis study was motivated by the importance of mathematical connection ability for elementary school students. It was necessary to develop an instrument that suitable the indicators of mathematical connection ability to understand the students' mathematical connection ability. The goal of this research was to develop an appropriate mathematical connection ability instrument for primary school students. This study was applied using Research and Development. The participants were 34 third-grade students at an elementary school in Purwakarta, SDN Nagrikaler, chosen through purposive sampling. The instrument was an essay test consisting of six open questions about whole numbers. The indicators developed in composing questions were related to the mathematical connection ability, namely connections inter topics in mathematics, other subjects, and everyday life. The questions were made beforehand in the expert judgment, then tested to see the validity, reliability, difficulty index, and discrimination power index. The validity test analysis indicated that six items on the instrument were valid, the reliability of the test instruments was very high. Meanwhile, the difficulty level was classified as difficult and moderate, and the discrimination power was also categorized as good and very good criteria. Thus, those six developed questions could be applied to measure mathematical connections in the topic of operations of whole numbers for second-grade elementary school students and were suitable for further research instruments on similar subjects and variables even at different times and places.AbstrakPenelitian ini dilatarbelakangi oleh pentingnya kemampuan koneksi matematis bagi siswa sekolah dasar. Penelitian ini bermaksud mengembangkan instrumen yang sesuai dengan indikator kemampuan koneksi matematis untuk memahami kemampuan koneksi matematis siswa. Penelitian ini bertujuan untuk mengembangkan instrumen kemampuan koneksi matematis yang sesuai untuk siswa sekolah dasar. Penelitian ini menggunakan metode Research and Development. Partisipan adalah 34 siswa kelas III SD di Purwakarta, SDN Nagrikaler, yang dipilih secara purposive sampling. Instrumen yang digunakan adalah tes esai yang terdiri dari enam pertanyaan terbuka tentang bilangan cacah. Indikator yang dikembangkan dalam menyusun soal berkaitan dengan kemampuan koneksi matematis, yaitu koneksi antar topik dalam matematika, mata pelajaran lain, dan kehidupan sehari-hari. Soal-soal tersebut dibuat terlebih dahulu sesuai saran expert, kemudian diuji untuk melihat validitas, reliabilitas, indeks kesukaran, dan indeks daya diskriminasi. Analisis uji validitas menunjukkan bahwa enam item pada instrumen tersebut valid dan reliabilitas instrumen tes sangat tinggi. Sedangkan tingkat kesukaran tergolong sukar dan sedang, dan daya pembedanya juga termasuk kriteria baik dan sangat baik. Dengan demikian, 6 item soal yang dikembangkan tersebut dapat diterapkan sebagai instrumen untuk mengukur koneksi matematis dalam pembelajaran matematika pada topik operasi hitung bilangan cacah terhadap siswa kelas dua SD dan layak digunakan untuk instrumen penelitian selanjutnya pada subjek dan variable sejenis meskipun pada waktu dan tempat berbeda.